Residential and Social Vulnerability in the San Francisco Neighbourhood of Villena (Alicante, Spain) - Francisco José Morales Yago; José Manuel Jurado Almonte; María José Cuesta Aguilar (Geographies)
Residential vulnerability in urban spaces is a complex phenomenon subject to a variety of social and economic factors. An example of this scenario is the San Francisco neighbourhood in Villena (Alicante, Spain). This is an area of residential vulnerability because of low levels of education among the population, low income, precarious housing and public insecurity. The main goal in this study was to analyse the profile of the neighbourhood using a mixed methodology based on statistical consultations with several official bodies and a qualitative method derived from surveys conducted with experts and interviews with focus groups made up of specialists, politicians and residents. The most significant results included the demographic stagnation of the local population and, conversely, a rejuvenation of the population thanks to foreign immigration, shaping a multicultural space not free of conflict, exclusion and residential precariousness. New challenges for integration towards a more participatory and safer coexistence emerged, with strategies aimed at curbing abandonment, preventing unlawful occupation of properties and contributing to residential and social regeneration.